Belize, Right Choices Bright Future : Systematic Country Diagnostic - Carneiro, Francisco (World Bank, Washington, DC, 2016)
This systematic country diagnostic (SCD) discusses on Belize’s ability to promote faster poverty reduction and greater shared prosperity which will depend on how well the country deals with its main sources of vulnerability. The main areas in need of a big push that could have the highest potential impact on the twin goals are : (i) improving education and skills; (ii) addressing crime and violence; and, (iii) increasing resilience to climate change and natural disasters. Strengthening resilience to natural disasters and climate change along with improvements in the existing infrastructure in Belize are critical to support the twin goals to end extreme poverty, and promote shared prosperity in poorer segments of society. Sustainable progress towards the achievement of the twin goals of reducing poverty and boosting shared prosperity in Belize will also require prioritizing fiscal sustainability. This SCD is structured in six chapters that range from a brief description of the main features of Belize to the discussion of priorities for growth and shared prosperity. Chapter 1 presents the country context, highlighting Belize’s main features as a small upper middle income country that faces high volatility associated with its size and vulnerability to exogenous shocks. Chapter 2 discusses trends in poverty and shared prosperity. Chapters 2 through 5 discuss the main underlying factors that have been found to influence Belize’s growth performance as well as its economic, social and environmental sustainability. Each of these chapters discuss in greater detail the nature of the challenges, dig deeper into exploring the likely causes of these challenges, and identify policy areas that could be critical for boosting growth and inclusion and ensuring sustainability. These chapters also identify knowledge and data gaps on areas where new information could help strengthen a diagnosis and inform specific actions in the priority areas. The sixth and final chapter has three important and distinctive features. First, it provides a synthesis of the analysis and findings of the previous chapters. Second, it provides a discussion of the approach used to identify the priorities for action in Belize. And, third, it concludes with a discussion of the priorities to boost shared prosperity and ensure economic, social and environmental sustainability in Belize.